Neutrophil AKT2 regulates heterotypic cell-cell interactions during vascular inflammation - Li, Jing (American Society for Clinical Investigation, 2014)
Interactions between platelets, leukocytes, and activated endothelial cells are important during microvascular occlusion; however, the regulatory mechanisms of these heterotypic cell-cell interactions remain unclear. Here, using intravital microscopy to evaluate mice lacking specific isoforms of the serine/threonine kinase AKT and bone marrow chimeras, we found that hematopoietic cell–associated AKT2 is important for neutrophil adhesion and crawling and neutrophil-platelet interactions on activated endothelial cells during TNF-α–induced venular inflammation. Studies with an AKT2-specific inhibitor and cells isolated from WT and Akt KO mice revealed that platelet- and neutrophil-associated AKT2 regulates heterotypic neutrophil-platelet aggregation under shear conditions. In particular, neutrophil AKT2 was critical for membrane translocation of αMβ2 integrin, β2-talin1 interaction, and intracellular Ca(2+) mobilization. We found that the basal phosphorylation levels of AKT isoforms were markedly increased in neutrophils and platelets isolated from patients with sickle cell disease (SCD), an inherited hematological disorder associated with vascular inflammation and occlusion. AKT2 inhibition reduced heterotypic aggregation of neutrophils and platelets isolated from SCD patients and diminished neutrophil adhesion and neutrophil-platelet aggregation in SCD mice, thereby improving blood flow rates. Our results provide evidence that neutrophil AKT2 regulates αMβ2 integrin function and suggest that AKT2 is important for neutrophil recruitment and neutrophil-platelet interactions under thromboinflammatory conditions such as SCD.